High school basic life support training: Is the trainer's experience of cardiopulmonary resuscitation in the actual setting important? A randomized control trial - Ali Sanati; Ali Ansari Jaberi; Tayebeh Negahban Bonabi (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Although basic life support (BLS) has been taught in school by a variety of professionals, it is still unclear that, whether the instructor's previous cardiopulmonary resuscitation (CPR) experience is an important factor. This study aimed to compare the effect of BLS training, based on trainer experience in actual situations, on knowledge and skills of secondary high school students. MATERIALS AND METHODS: In this randomized controlled trial, 150 high school students were selected based on the inclusion criteria and then assigned into two groups, (76 in Group A), and (74 in Group B) randomly. Both groups were trained according to adult BLS: 2020 American Heart Association guidelines on mannequins in three 60 min in-person training sessions. The knowledge and skill scores were measured for both groups before, immediately, and 1 month after intervention by a questionnaire. Data were analyzed by the SPSS software version 22, using Chi-square, Mann-Whitney U, repeated-measure ANOVA tests, and statistically modeling at a significance level of 0.05. RESULTS: There were no significant differences between groups regarding demographic characteristics. The knowledge and skill scores in both groups increased significantly compared to baseline immediately and 1 month after the intervention (P = 0.001). However, there was no significant difference in knowledge scores between groups (P = 0.076(. However, at the immediacy and 1 month after the intervention, the skill score in "Group A" was significantly higher than the "Group B" (P = 0.001). CONCLUSIONS: The trainer's experience of CPR in the actual setting in the transfer of BLS knowledge is not important, but it improved Student's BSL skill acquisition score.